Membentuk Lembaga Pendidikan Unggul: Peran Kepemimpinan Transformasional Dalam Meningkatkan Kinerja Guru - Hanifia Izzah Rahmadanty; Zahrotul Mufarihah; Nadlirotul Maulidia; Ahmad Tajuddin Az Zaki (CV. ITTC INDONESIA, 2024)
An organization or institution needs a leader who can influence its subordinate members. A leader who has a good leadership spirit will be able to maximize his performance so that the desired goals can be realized. This research aims to find out the role of transformational leadership in improving the performance of teaching staff. Organizations and institutions need transformational leaders whose implementation, a leader can provide influence through modeling, motivation, inspiration and morals. This study uses the library research method to explore more information about transformational leadership style and its relationship to the world of education. This research produces an understanding of the definition of transformational leadership, principles, components, and knowing the advantages and disadvantages of this leadership style and also provides insight into the role of transformational leadership in improving the performance of teaching staff in the world of education.